Association of Factor VII:C Levels with Environmental and Genetic Factors in Patients with Ischaemic Heart Disease and Coronary Atheroma Characterised by Angiography - Heywood, Daniella M; Ossei-Gerning, Nicholas; Grant, Peter J (Thrombosis and Haemostasis, 1996)
Elevated Factor VII:C (FVII:C) levels are an independent risk factor for acute myocardial infarction. To examine the association between FVII:C levels, genetic and environmental factors in patients with a history suggestive of ischaemic heart disease, 270 patients were studied. FVII:C levels were significantly associated with the Msp I and promoter insertion polymorphisms. FVII:C correlated with environmental factors, and these correlations remained when analysed by genotype. In a multiple regression model, genotype, body mass index, cholesterol, triglycerides and gender remained as independent and significant predictors of FVII:C levels. There was no significant difference in FVII:C concentrations with severity of atheroma, or in patients with a history of myocardial infarction. These findings provide further evidence linking FVII:C with Msp I and promoter insertion genotypes and with environmental factors in established IHD, but suggest there is not a genotype-environment interaction or a relationship between FVII:C levels and severity of ischaemic heart disease.